PENINGKATAN HASIL BELAJAR LOMPAT JAUH MELALUI PERMAINAN LOMPAT KANCIL PADA SISWA KELAS IV SDN JAMBANGAN 02 KABUPATEN BATANG TAHUN PELAJARAN 2012 / 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2013)
Based on observations of the learning process athletics, especially the long jump at the fourth grade students ofSD Negeri Jambangan not going well, because the students' interest in learning the long jump less. From thedescription of the problem, the authors strive to increase learning outcomes through the game long jumpjumping deer that aims to improve learning outcomes in the long jump Elementary School fourth gradestudents through application modification Jambangan 02 deer jumping game. With the formulation of theproblem as follows: "Is the application of deer jumping games can improve learning outcomes in the long jumpElementary School fourth grade students Onion Pot Batang District 02 school year 2012/2013?The researchers plan a study using action research methods class. The design of classroom action research wasconducted in two cycles with stages of planning, action, observation and reflection. The subjects were fourthgrade students of SD Negeri 02 Sub Onion Pot Batang. Data collection techniques using the test methods,methods of documentation, and questionnaires. In the first cycle increased student mastery of learning outcomesby the number of students who achieve mastery learning of 20 students 15 students that scored ≥ 70, with a75% passing grade on the second cycle and the number of students who achieve mastery learning increased to90% of 18 students who received grades ≥ 70, when viewed from the mastery learning in the first cycle andsecond cycle there are only 2 students who do not achieve mastery learning. Conclusions from this research islearning through games deer can jump long jump improve learning outcomes Elementary School fourth gradestudents district Onion Pot 02 Lessons Batang year 2012/2013. Suggestions researchers includes several things,namely: (1) deer jumping game can be an alternative for teachers to be applied to the material Penjasorkes longjump, (2) the teacher should be able to follow in order to condition students with effective learning, and not toolong so it takes time to play lesson.